2021
DOI: 10.1038/s41598-021-91670-w
|View full text |Cite
|
Sign up to set email alerts
|

Copper-binding anticancer peptides from the piscidin family: an expanded mechanism that encompasses physical and chemical bilayer disruption

Abstract: In the search for novel broad-spectrum therapeutics to fight chronic infections, inflammation, and cancer, host defense peptides (HDPs) have garnered increasing interest. Characterizing their biologically-active conformations and minimum motifs for function represents a requisite step to developing them into efficacious and safe therapeutics. Here, we demonstrate that metallating HDPs with Cu2+ is an effective chemical strategy to improve their cytotoxicity on cancer cells. Mechanistically, we find that prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 125 publications
(245 reference statements)
2
23
0
Order By: Relevance
“…Third, while the peptide and glycolipid are individually able to disrupt membranes, the integration of both in the membrane produces a dramatic structural rearrangement of the membrane, as shown by XRD. The decrease in the bilayer thickness, which surpasses any such effects for the peptides alone under the same measurement conditions, ,, is consistent with the presence of SL-HE and piscidin in the membrane, in agreement with the MS (SL-HE signal in Figure ) and solid-state NMR (piscidin signal in Figure ) data. Based on the SPR data described above, flowing both SL-HE and piscidin onto the membrane produces a cooperative mass increase.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Third, while the peptide and glycolipid are individually able to disrupt membranes, the integration of both in the membrane produces a dramatic structural rearrangement of the membrane, as shown by XRD. The decrease in the bilayer thickness, which surpasses any such effects for the peptides alone under the same measurement conditions, ,, is consistent with the presence of SL-HE and piscidin in the membrane, in agreement with the MS (SL-HE signal in Figure ) and solid-state NMR (piscidin signal in Figure ) data. Based on the SPR data described above, flowing both SL-HE and piscidin onto the membrane produces a cooperative mass increase.…”
Section: Discussionsupporting
confidence: 85%
“…14 Cu 2+binding enhances significantly the antimicrobial and anticancer activities of P1 and P3. 46,53,78 It has also been found that the two HDPs, magainin and PLGa, interact with membranes in a way that stabilizes the insertion of PLGa in a transmembrane orientation, an effect that correlates with synergistic effects on bacteria. 142,143 Physical association between two antimicrobial agents represents an advantage if it can be maintained in vivo to ensure that the compounds can exert concerted action spatially and temporally.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Regardless, the absence of change in MIC to ampicillin strengthens the notions that PUFA incorporation can alter bacterial susceptibility to membrane targeting antibiotics. Related studies have characterized the activity of fish antimicrobial peptides, such as piscidins, on Gram‐negative bacteria (Comert et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Binding divalent metals such as copper and zinc have regulated the antimicrobial activity of the peptide. Piscidin 1& 3 peptides from fish mast cells had improved antibacterial activity, membrane insertion, and increased cytotoxicity against cancer cells when chelated with copper Cu 2+ (195,196). The antibacterial activity was improved upon the zinc Zn2+ to ClavaninA, demonstrating the ability to cleave the bacterial chromosomal DNA (197).…”
Section: Other Techniquesmentioning
confidence: 99%